Bacteriological Profile of Urinary Tract Infection in Children of a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2018)
Background: Urinary tract infection (UTI) is an important cause of morbidity and mortality in the paediatric age group. The spectrum of etiologic agents causing UTI and their antimicrobial resistance pattern has been continuously changing over the years. It varies among geographical locations, hospitals and also in different age groups.Objective: The aim of this study was to find out the causative agents of UTI and their antibiotic sensitivity pattern in paediatric patients in CMH, Dhaka.Methodology: This is an observational cross sectional study. A total of 180 children aged 0 months to 15 years attending pediatric outpatient department or admitted in Department of Paediatrics CMH, Dhaka with suspected UTI were subjected for urine routine and microscopic examination between June 2015 to May 2016. Those having pyuria (n=120) were then sent for urine culture and sensitivity to the laboratory of Armed Forces Institute of Pathology (AFIP). Patients having significant growth of organism were enrolled as cases of confirmed UTI. After enrollment, relevant information such as age, sex, sociodemographic profile was obtained and recorded in case record form.Result: In the present study, urine routine microscopy was done in all 180 cases of suspected UTI. Among all urine analysis 67% had significant pyuria (n=120). Of the 120 cases with pyuria, 58 cases were having culture positive accounting 48.3% of the total sample studied. Occurrence of urinary tract infections was highest in the age group below 5 year (62.5%). UTI was more prevalent in girls (63.3%) with male to female ratio 1:1.7. E. coli was the commonest isolate (62.1%) followed by Enterococcus (19.2%) and Klebsiella (10.2%). E. coli was found to be most sensitive to Ciprofloxacin, Nitrofurantoin, Amikacin, and Levofloxacin in descending order. There was a generally high level of resistance of isolates to Cotrimoxazole, Amoxycillin, Aminoglycosides, Azythromycin and the Cephalosporins like Cefuroxime, Ceftazidime, Cefixime and Ceftriaxone compared to Ciprofloxacin, Nitrofurantoin and Levofloxacin.Conclusion: Based on our findings, Ciprofloxacin, Levofloxacin and Nitrofurantoin are appropriate for initial empirical therapy for UTI among Bangladeshi children.Bangladesh J Child Health 2017; VOL 41 (2) :77-83